Pengaruh Citra Toko Dan Kepercayaan Toko Terhadap Loyalitas Konsumen Pada Toko Station Game Di Tenggarong - Ramadhani, Rahmat; Iskandar, Iskandar; Luthman, Awang Yacoub (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2018)
Abstract :Toko Station Game Tenggarong which is a branch of Station Celular Samarinda which serves the sale and purchase of mobile phones and accessories that are located on the lake Semayang RT.12 Kelurahan Melayu Tenggarong District. The goods are sold at Tenggarong Station Station Shop directly imported from jakarta and surabaya. The purpose of this study is to find out whether the variables of Store Image and Store Trust affect simultaneously to Consumer Loyalty At Station Station Game In Tenggarong, to find out, Are the variables of Store Image and Store Trust partially influence on Consumer Loyalty At Station Station Game Di Tenggarong and to know, Among the independent variables are the variables which have the most dominant influence on the Consumer Loyalty At Station Stores Game In Tenggarong? From both result of partial correlation test above seen value of Scitra variable of store bigger influence than store trust variable, so store image variable is the most dominant variable influence to consumer loyalty. From the description, it can be concluded that the second hypothesis in this study "That, Variable Image of Stores Which Has The Dominant Influence On Consumer Loyalty At Station Game Stores In Tenggarong" in accepted and proven truth. Â Keywords: Consumer Loyalty, Store Image And Store Trust